English historical linguistics change in structure and meaning : papers from the xxth ICEHL - Los, Bettelou; Cowie, Claire (Claire Susan); Honeybone, Patrick (Patrick George); Trousdale, Graeme, 1971- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2022)
"This volume contains a set of articles based on papers selected from those delivered at the 20th International Conference on English Historical Linguistics (ICEHL, Edinburgh 2018). It focuses on cutting-edge research in the history of English, while reflecting the diversity that exists in the current landscape of English historical linguistics. Chapters showcase traditional as well as novel methodologies in historical linguistics (the latter made possible by the increasing quality and accessibility of digital tools), work on linguistic interfaces (between segmental phonology and prosody, and syntax and information structure) and work on mechanisms of language change (such as Yang's Tolerance Principle, on the threshold for the productivity of linguistic rules in language acquisition). The volume will be of interest to those working on the historical phonology, morphology, syntax and pragmatics of English, language change, corpus linguistics, computational historical linguistics, and related sub-disciplines"--